Assessment of ZnO and SiO(2) nanoparticle permeability through and toxicity to the blood–brain barrier using Evans blue and TEM - Shim, Kyu Hwan (Int J Nanomedicine, 2014)
As increasing variants of nanoparticles (NPs) are being used in various products, it has become apparent that size alone can no longer adequately explain the variety of generated toxic profiles. Recent studies with NPs have suggested that various sizes of NPs could determine in vitro toxicity. In an attempt to address concerns regarding neurotoxicity of zinc oxide (ZnO) and silica (SiO(2)) NPs, these were examined after exposing them via oral, dermal, and intravenous administrations of NPs and their toxicological effects on the brain over a prescribed period of time were assessed. After 28 days of repeated oral administrations of ZnO or SiO(2) independently, possibly due to damages to the blood brain barrier (BBB), neurotoxicity, were investigated by Evans blue technique. Next, in order to assess whether ZnO NPs could compromise the BBB, ZnO NPs were intravenously injected on day 0, 7, 14, 21 and 28 no further treatment was administered for 62 days. Deposition of SiO(2) in brain from repeated dermal and oral administrations for 90 days were evaluated by transmission electron microscopy coupled with scanning energy-dispersive X-ray spectroscopy. Physiochemical profiles were principally determined on particle size at the beginning of the current toxicity investigations on ZnO and SiO(2) NPs. The BBB was found to be intact after independent repeated oral administrations of ZnO or SiO(2) NPs for 28 days, suggesting no significant damage. Neuronal death was also not observed after the intravenous administrations of ZnO NPs. After 90 days of repeated dermal and oral administration of SiO(2) NPs, no deposition of NPs was observed in hippocampus, striatum, and cerebellum regions using transmission electron microscope analyses. These observations suggest that the BBB was not compromised and was able to block penetration of ZnO and SiO(2) NPs, resulting in significant neurotoxic effects. Moreover, absence of SiO(2) in three regions of brain after dermal and oral administrations for 90 days suggested that brain was protected from SiO(2). No behavior change was observed in all studies, suggesting that 90 days may not be long enough to assess full neurotoxicity of NPs in vivo.